Semantic Field as a Fragment of National World Language Picture - Bezkorovaynaya, G.T. (Vestnik Rossijskogo universiteta družby narodov. Seriâ: Teoriâ âzyka, semiotika, semantika (Online), 2017)
The article considers the semantic field gentleness/nobleness as a fragment of the English national world picture. The semantic fields are the structures that constitute the general semantic sphere of any language. In course of the analysis of so important for Englishmen semantic field, the history and features of the field constituents are defined. The role of the concept gentleman is studied. The conclusion about the extra-lingusitic aspect as a crucial factor for abstract concepts creating is made. The study of national world pictures by means of semantic fields makes it possible to understand the view of the world of different nations.